Kentucky High Schools with SROs and Without: An Examination of Criminal Violation Rates. Issue 6 (November 2017) - Sullivan, William J.; Hausman, Charles S.
School violence has become a focal point, sparked by violent mass killings throughout the nation. One of the most substantial efforts for improving school safety and security is the utilization of specially trained police, titled school resource officers (SROs). Regardless of the importance of maintaining safe schools and an environment that is conducive to learning, relatively little research has been conducted examining the effectiveness of these programs and the variables that may influence those findings (Raymond, 2010). This research uses two studies focused on the association of SROs and reported criminal violation rates at Kentucky high schools. Findings indicate no statistically significant differences in reported criminal violation rates between high school populations without SROs and those with full-time SROs. Implications of these findings are discussed in addition to how SRO presence may affect the frequency and accuracy of reported criminal violations.